Effects of Rapid Weight Loss on Systemic and Adipose Tissue Inflammation and Metabolism in Obese Postmenopausal Women - Alemán, José O.; Iyengar, Neil M.; Walker, Jeanne M.; Milne, Ginger L.; Da Rosa, Joel Correa; Liang, Yupu; Giri, Dilip D.; Zhou, Xi Kathy; Pollak, Michael N.; Hudis, Clifford A.; Breslow, Jan L.; Holt, Peter R.; et al. (Journal of the Endocrine Society, 2017)
Context:Obesity is associated with subclinical white adipose tissue inflammation, as defined by the presence of crown-like structures (CLSs) consisting of dead or dying adipocytes encircled by macrophages. In humans, bariatric surgery-induced weight loss leads to a decrease in CLSs, but the effects of rapid diet-induced weight loss on CLSs and metabolism are unclear.Objective:To determine the effects of rapid very-low-calorie diet-induced weight loss on CLS density, systemic biomarkers of inflammation, and metabolism in obese postmenopausal women.Design:Prospective cohort study.Setting:Rockefeller University Hospital, New York, NY.Participants:Ten obese, postmenopausal women with a mean age of 60.6 years (standard deviation, ±3.6 years).Main Outcome Measures:Effects on CLS density and gene expression in abdominal subcutaneous adipose tissue, cardiometabolic risk factors, white blood count, circulating metabolites, and oxidative stress (urinary isoprostane-M) were measured.Results:Obese subjects lost approximately 10% body weight over a mean of 46 days. CLS density increased in subcutaneous adipose tissue without an associated increase in proinflammatory gene expression. Weight loss was accompanied by decreased fasting blood levels of high-sensitivity C-reactive protein, glucose, lactate, and kynurenine, and increased circulating levels of free fatty acids, glycerol, β-hydroxybutyrate, and 25 hydroxyvitamin D. Levels of urinary isoprostane-M declined.Conclusion:Rapid weight loss stimulated lipolysis and an increase in CLS density in subcutaneous adipose tissue in association with changes in levels of circulating metabolites, and improved systemic biomarkers of inflammation and insulin resistance. The observed change in levels of metabolites (i.e., lactate, β-hydroxybutyrate, 25 hydroxyvitamin D) may contribute to the anti-inflammatory effect of rapid weight loss.Rapid diet-induced weight loss increases subcutaneous adipose crown-like structure density in obese postmenopausal women.